Paris as ‘Other’: George Moore, Kate Chopin and French literary escape routes - Pierse, Mary S. (ABEI Journal, 2006)
Even by as late as the 1890s, France – and especially Paris – represented what was other for Victorian society. This paper claims that Parisian pictures, as drawn by George Moore (notably in Celibates and Esther Waters) and Kate Chopin (in “Lilacs”), constitute gentle challenges to simplistic judgment and fundamentalist prejudice. Their portrayals are word pictures without the expected accompaniment of an obvious edifying lesson; they are neither overt nor threatening while, with dispassionate balance, they advance an insidiously persuasive case for reinterpretation of Victorian moral certainties. This essay further suggests that the Irishness of both writers may be a key factor in their artistic and modernist approaches.